Speech intelligibility in patients with oral cancer: An objective baseline evaluation of pretreatment function and impairment - Stelzle, Florian; Oetter, Nicolai; Göllner, Luisa; Adler, Werner; Rohde, Maximilian; Maier, Andreas; Matthies, Levi; Kesting, Marco Rainer; Knipfer, Christian (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2019)
Background This study seeks to identify those factors that influence the pre-therapeutic speech intelligibility in patients with oral squamous cell carcinoma (OSCC).
CRIS-Team WoS Importer:2019-04-04